Treatment withdrawal of the patient on end of life: An analysis of values, ethics and guidelines in palliative care - Daniel A. Nnate (Wiley, 2021)
Abstract Aim Family surrogate decision‐making during the later stage of a patient's life may sometimes result in conflict and emotional distress among the parties involved. The present article aims to promote ethical end‐of‐life decision‐making among healthcare professionals in a view to eliminating any misunderstanding that may arise while meeting the care needs of the patient. Design A case study involving a request for treatment withdrawal by the family of a patient on end of life. Methods This paper draws upon a scenario encountered during practice to analyse the moral commitments in delivering high‐quality end‐of‐life care with much emphasis on pre‐existing palliative care guidelines for adults. Results Healthcare professionals are bound by the principle of beneficence, non‐maleficence, autonomy and justice. Although the use of guidelines may be tenable, decisions often take into consideration the patient's choice and then weighed against the moral values of healthcare specialists and those required in the profession.